Should Big Topics in Sociology be Studied? - Gleb Novikov (Journal of Economic Sociology, 2016)
The new season of weekly seminars of the Laboratory for Studies in Economic Sociology started on September 6, 2016. The department head and first vice rector of HSE, Vadim Radaev, was a speaker, and his presentation explored links between concrete empirical studies and “broad topics” in sociology. Radaev suggested looking for topics that are not separate from empirical findings and connect many subject areas. A draft research project was considered as an illustrative example. The point was to relate a decrease in alcohol consumption by Millennials (those born in 1982–1999) to larger-scale social shifts and potentially to the withering away of a “Soviet common man” from the position of a dominant social type. Alcohol consumption was chosen as an indicator because of its close relationship to multiple life spheres: healthcare, politics, economy, everyday communication, etc. The paradox is that despite enjoying favorable conditions for drinking, Millennials consume about two times less alcohol than previous generations. By applying a cohort analysis to illuminate this paradox, Vadim Radaev attributed it to massive sociocultural changes in post-Soviet Russia.The presentation included a lively discussion of both methodical issues and general methodological considerations. The discussion was carried out by laboratory researchers Elena Berdysheva, Dilyara Ibragimova, Anna Kruglova, Olga Kuzina, Andrey Shevchuk, and numerous HSE students.